The Arrival - Tan, Shaun (Hodder Children's Books, 2007)
What drives so many to leave everything behind and journey alone to a mysterious country, a place without family or friends, where everything is nameless and the future is unknown? This silent graphic novel is the story of every migrant, every refugee, every displaced person, and a tribute to all those who have made the journey.